Nasopharyngeal carcinoma in a six-year-old female child: a case report - Swain, Santosh Kumar; Samal, Smrutipragnya; Sahu, Mahesh Chandra (Pediatria Polska - Polish Journal of Paediatrics, 2019)
Nasopharyngeal carcinoma (NPC) is an extremely rare malignancy among the paediatric age group. The relative rarity of paediatric NPC makes the diagnosis difficult. Consequently, NPC tends to be locally advanced at the time of diagnosis in the paediatric age group and is sometimes associated with distant metastasis. The diagnosis of paediatric NPC should prompt immediate treatment. We report a case of undifferentiated nasopharyngeal carcinoma in a young girl who presented with advanced loco-regional disease and was treated with chemoradiation.